Kebijakan Kurikulum Pendidikan Islam Pada Satuan Pendidikan Dasar, Menengah dan Tinggi - Rina Nirwana; Qolbi Khoiri (Journal on Education, 2023)
The purpose of this paper is to examine Islamic education curriculum policies in elementary, secondary and tertiary units using library research methods. The results of the study in this writing show that the Islamic education curriculum policy, especially in Indonesia, has undergone several changes. Changes that occur adapt to the circumstances and the needs of the times. The development of the Islamic curriculum from the beginning of the history of education in Indonesia in 1945 after Indonesian independence was discussed in three periods; first, during the old order there were three changes, namely the 1947, 1952 and 1964 curricula; Second, during the New Order era, four changes were made, namely the 1968, 1975, 1984 and 1994 curricula; Third, there were four changes during the reformation period and those that are still used today are the 2004 Curriculum (KBK), the 2006 Curriculum (KTSP), the 2013 Curriculum and the independent learning curriculum. The Islamic religious education curriculum in each education unit is discussed from: First, the arrangement of the madrasah curriculum which consists of (Madrasah Ibtidaiyah, Madrasah Tsanawiyah and Madrasah Aliyah) which follows National Education System Law 20 of 2003; Second, the rules for the pesantren curriculum follow Law no. 18 of 2019